2015
DOI: 10.1186/s12862-015-0516-9
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic history and high-elevation adaptations inferred from the mitochondrial genome of Glyptosternoid fishes (Sisoridae, Siluriformes) from the southeastern Tibetan Plateau

Abstract: BackgroundThe distribution of the Chinese Glyptosternoid catfish is limited to the rivers of the Tibetan Plateau and peripheral regions, especially the drainage areas of southeastern Tibet. Therefore, Glyptosternoid fishes are ideal for reconstructing the geological history of the southeastern Tibet drainage patterns and mitochondrial genetic adaptions to high elevations.ResultsOur phylogenetic results support the monophyly of the Sisoridae and the Glyptosternoid fishes. The reconstructed ancestral geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 66 publications
(81 reference statements)
7
37
2
Order By: Relevance
“…These conflicting phylogenies were weakly supported, possibly resulting from the use of inadequate genetic information. Recently, a well-supported molecular phylogeny of the Sisoridae, based on the complete mitochondrial genomes of a few sisorid species, has become available [ 9 , 10 ]. However, a robust phylogeny including all 12 genera of the Chinese sisorid catfishes remains unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…These conflicting phylogenies were weakly supported, possibly resulting from the use of inadequate genetic information. Recently, a well-supported molecular phylogeny of the Sisoridae, based on the complete mitochondrial genomes of a few sisorid species, has become available [ 9 , 10 ]. However, a robust phylogeny including all 12 genera of the Chinese sisorid catfishes remains unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, an endemic blind stone loach, Triptophysa xiangxiensis Yang Yuan & Liao, occurs in the adjacent drainage, upper Youshui River, another tributary of Lake Dongting . The schizothoracin, Triplophysa and glyptosternoid fishes are typically associated with the uplift of the Tibetan Plateau (Hora & Silas 1952a;Ma et al 2015). These new records represent the easternmost extent of the schizothoracine and glyptosternoid species distributions.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have reported on the mechanisms of osmoregulation acclimation or habitat changes in fish, such as Salmonids (Boeuf, ; Folmar Lc, ), green sturgeon (Allen, Cech, & Kultz, ), European eels (Kalujnaia et al., ; Tseng & Hwang, ), cichlid fish (Febry, ; Whitehead, ; Xia et al., ) and also in mammals, e.g., the riverine odontocetes (Caballero, Duchene, Garavito, Slikas, & Baker, ), the killer whales (Orcinus orca) (Foote et al., ). Some genes were reported to associate with osmoregulation acclimation in fish, such as the COX1 of Glyptosternoid fish in China (Ma, Kang, Chen, Zhou, & He, ) and NADH Dehydrogenase genes and cytochrome b of the schizothoracine fish (Cyprinidae) (Li et al., ). In tilapia, some osmoregulation associated genes have been identified, such as transferrin gene, β ‐Hemoglobin , Ca2+transporting plasma membrane ATPase , pro‐opiomelanocortin, beta‐actin (Rengmark & Lingaas, ), prolactin (Streelman & Kocher, ).…”
Section: Discussionmentioning
confidence: 99%